Asprosin Increases Sexual Instinct in Male Rats - Tan, Fatih; Oz, Zeynep Dila; Ozdede, Mehmet Ridvan; Zorlu, Gokhan; Avcu, Gaye Goksu; Yasar, Abdullah; Kelestimur, Haluk (Wiley, 2023)
[Abstract Not Available]
Keywords: Asprosin; Scent; Oxytocin; Non-contact Erection Test